Spotlight on Data Data Storytelling with Mico Yuk - Yuk, Mico (O'Reilly Media, Inc., 2019)
The power of storytelling has long been used in Hollywood to engage viewers and generate billions of dollars in sales. However, data storytelling, while highly trendy, is frequently misused and often limited to pretty charts. In this Spotlight on Data, learn how to use the power of storytelling with your data to skyrocket user engagement. Get your users to take action by implementing a few proven techniques. Recorded on July 15, 2019. See the original event page for resources for further learning. Find future live events to attend or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Data, you'll learn about, discuss, and debate the tools, techniques, questions, and quandaries in the world of data. You'll discover how successful companies leverage data effectively and how you can follow their lead to transform your organization and prepare for the Next Economy.